2016
DOI: 10.1371/journal.pgen.1006468
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel L-rhamnose Uptake Transporter in the Filamentous Fungus Aspergillus niger

Abstract: The study of plant biomass utilization by fungi is a research field of great interest due to its many implications in ecology, agriculture and biotechnology. Most of the efforts done to increase the understanding of the use of plant cell walls by fungi have been focused on the degradation of cellulose and hemicellulose, and transport and metabolism of their constituent monosaccharides. Pectin is another important constituent of plant cell walls, but has received less attention. In relation to the uptake of pec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 84 publications
(100 reference statements)
2
26
0
Order By: Relevance
“…Release, uptake and metabolism of another building block of pectin, L-rhamnose, is regulated by RhaR 15 , 22 . Gruben et al .…”
Section: Introductionmentioning
confidence: 99%
“…Release, uptake and metabolism of another building block of pectin, L-rhamnose, is regulated by RhaR 15 , 22 . Gruben et al .…”
Section: Introductionmentioning
confidence: 99%
“…An L-rhamnose transporter (RhtA) has been characterized recently in A. niger [ 6 ]. Interestingly, it has been found that rhtA is co-localized with the α-L-rhamnosidase gene rhaB .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it has been found that rhtA is co-localized with the α-L-rhamnosidase gene rhaB . The transcriptional profile of rhtA and rhaB genes during a time-course growth experiment of A. niger on L-rhamnose suggests not only that there is a coordinated role in the release and the transport of L-rhamnose during consumption but also that strong activation of these two genes do not require high concentrations of L-rhamnose but only low levels [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…the standard Blast algorithm) are in many cases not precise enough (Mishra et al, 2014;Sloothaak et al, 2016a). The use of profile hidden Markov models (HMM) to segregate sugar transporter proteins based on their substrate has been shown as an effective approach, however their precision largely depends on the availability of a consistent training set of biochemically characterized proteins with the function of interest (Sloothaak et al, 2015(Sloothaak et al, , 2016a. In this study we aimed, for the first time, to identify a eukaryotic L-rhamnose transporter and consequently, no eukaryotic examples of L-rhamnose transporters were available in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In this experiment, the L-rhamnose uptake ability of the EBY.VW4000_RhtA strain was determined, using as a negative control the EBY.VW4000 strain expressing the A. niger specific D-xylose transporter XltB (Sloothaak et al, 2016a (Tate et al, 1992), however, the experimental approach used by Tate et al, which performed overnight cultivations of different E. coli strains (WT and L-rhamnose negative strains) for that purpose, make a comparison difficult. The L-rhamnose uptake rate determined for RhtA was, however, comparable to the maximum sugar uptake rate determined for other fungal MFS transporters, like the D-xylose transporters GXS1 from Candida intermedia (Young et al, 2012) or XylH from Debaryomyces hansenii (Ferreira et al, 2013).…”
Section: Determination Of the Rhta Ability To Transport L-rhamnosementioning
confidence: 99%